The Smell of Blue Light: A New Approach toward Understanding an Olfactory Neuronal Network - Störtkuhl, Klemens F.; Fiala, André (Frontiers in Neuroscience, 2011)
Olfaction is one of the most important senses throughout the animal kingdom. It enables animals to discriminate between a wide variety of attractive and repulsive odorants and often plays a decisive role in species specific communication. In recent years the analysis of olfactory systems both in vertebrates and invertebrates has attracted much scientific interest. In this context a pivotal question is how the properties and connectivities of individual neurons contribute to a functioning neuronal network that mediates odor-guided behavior. As a novel approach to analyze the role of individual neurons within a circuitry, techniques have been established that make use of light-sensitive proteins. In this review we introduce a non-invasive, optogenetic technique which was used to manipulate the activity of individual neurons in the olfactory system of Drosophila melanogaster larvae. Both channelrhodopsin-2 and the photosensitive adenylyl cyclase PAC α in individual olfactory receptor neurons of the olfactory system of Drosophila larvae allows stimulating individual receptor neurons by light. Depending on which particular olfactory receptor neuron is optogenetically activated, repulsion or attraction behavior can be induced, indicating which sensory neurons underlie which type of behavior.